2018
DOI: 10.14419/ijet.v7i4.20.22115
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Breast Cancer Using Logistic Regression and Multi-Class Classifiers

Abstract: The primary identification and prediction of type of the cancer ought to develop a compulsion in cancer study, in order to assist and supervise the patients. The significance of classifying cancer patients into high or low risk clusters needs commanded many investigation teams, from the biomedical and the bioinformatics area, to learn and analyze the application of machine learning (ML) approaches. Logistic Regression method and Multi-classifiers has been proposed to predict the breast cancer. To produce deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 18 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…Yet, the proposed feature selection techniques could be exercised over different datasets and observe their performances. Author Sultana et.al, [11] works on various data mining classification models namely LR, K-NN, K-Star, Decision table, Multi-Layer Perceptron (MLP), Multi-class Classifiers, Decision Trees, REP trees, and PART using breast cancer dataset. Results concluded that LR performed the best compared to other models with an accuracy of 97.3%, Root Mean Square Error (RMSE) of 014, True Positive (TP) of 0.97, False Positive (FP) of 0.03, ROC of 0.99, F1-score of 0.97, and model build time of 0.65 seconds.…”
Section: Literature Surveymentioning
confidence: 99%
“…Yet, the proposed feature selection techniques could be exercised over different datasets and observe their performances. Author Sultana et.al, [11] works on various data mining classification models namely LR, K-NN, K-Star, Decision table, Multi-Layer Perceptron (MLP), Multi-class Classifiers, Decision Trees, REP trees, and PART using breast cancer dataset. Results concluded that LR performed the best compared to other models with an accuracy of 97.3%, Root Mean Square Error (RMSE) of 014, True Positive (TP) of 0.97, False Positive (FP) of 0.03, ROC of 0.99, F1-score of 0.97, and model build time of 0.65 seconds.…”
Section: Literature Surveymentioning
confidence: 99%
“…In medicine, ref. [13][14][15] used logistic regression to predict breast cancer. Thottakkara et al [16] demonstrated that logistic regression is one of the best machine learning models for predicting postoperative sepsis and kidney injuries.…”
Section: Related Workmentioning
confidence: 99%
“…Jabeen sultana and Abdul Khader Jilani predicted the existance of Breast cancer by evaluating dataset on various classifiers like Multi-Layer Perceptron (MLP), Random Forest, Simple Logistic-regression method, IBK, K-star, Decision table, Decision Trees (DT), PART, Multi-Class Classifiers and REP Tree. Findings showed that Simple Logistic Regression was the best model followed by other methods [11]. Mohammed Abdulrazaq Kahya used the BreaKHis (The Breast Cancer Histopathological Images) datasets to develop a method to classify breast tumors into two classes benign and malignant.…”
Section: Litereture Reviewmentioning
confidence: 99%